Pengembangan Pengemasan dan Legalitas Produk UMKM Kripik Koe Bengkayang di Daerah Perbatasan - Yeremia Niaga Atlantika; Eligia Monixa Salfarini; Sabinus Beni; Totok Victor Didik Saputro; Maria Angela Siokalang (I-Com: Indonesian Community Journal, 2024)
Geographically, Bengkayang Regency borders Malaysia, offering advantages to Micro, Small, and Medium Enterprises (MSMEs) in the region. However, Kipik Koe Bengkayang MSME has not been able to fully capitalize on this potential due to suboptimal product packaging and the lack of a Business Identification Number (NIB). To address these issues, a community service project was conducted, focusing on hygienic packaging and production processes, as well as obtaining business legality to expand market reach. The methods employed included socialization and direct assistance through initial observation, scheduling, implementation, and evaluation. This initiative involved two owners of Kipik Koe Bengkayang MSME and consisted of three meetings. As a result, Kipik Koe Bengkayang produced more hygienic product packaging with its own brand label and successfully obtained an NIB. This community service project had a positive impact on improving packaging quality and hygienic production processes, as well as aiding the business development of Kipik Koe Bengkayang MSME through the issuance of business legality.